Reinterpreting Heroism: A queer Lens on Madeline Miller’s The Song of Achilles - Valerie, Clairine; Tamba, Mariana Cecilia; Siregar, Lailan Haz Anugrahyuni; Ayudhea, Fasya; Syahputra, Fikry Prastya (Universitas Pahlawan Tuanku Tambusai, 2025)
The Exploration of heroism and queer identity in literature is important for understanding today's values and emotional experiences. While many traditional stories focus on physical strength and bravery, there is a lack of research on how these ideas can be redefined through emotions and vulnerability. This study looks at Madeline Miller's The Song of Achilles, specifically how the story, told from Patroclus's viewpoint, changes the usual ideas of what it means to be a hero. Using a qualitative approach with close reading and textual analysis, the research shows how love and emotional connections are seen as heroic qualities. The main finding is that true heroism includes empathy and selflessness, challenging outdated masculine ideals. In conclusion, the study suggests that Miller’s fresh take encourages readers to adopt a broader view of heroism, highlighting the importance of emotional depth in our understanding of human experience.